Leaf and Community Photosynthetic Carbon Assimilation of Alpine Plants Under in-situ Warming - Zhou, Zijuan; Su, Peixi; Wu, Xiukun; Shi, Rui; Ding, Xinjing (Frontiers in Plant Science, 2021)
Background: The Tibetan Plateau is highly sensitive to elevated temperatures and has experienced significant climate warming in the last decades. While climate warming is known to greatly impact alpine ecosystems, the gas exchange responses at the leaf and community levels to climate warming in alpine meadow ecosystems remain unclear. Results: In this study, the alpine grass, Elymus nutans, and forb, Potentilla anserina, were grown in open-top chambers (OTCs) for three consecutive years to evaluate their response to warming. Gas exchange measurements were used to assess the effects of in-situ warming on leaf- and community-level photosynthetic carbon assimilation based on leaf photosynthetic physiological parameters. We introduced a means of up-scaling photosynthetic measurements from the leaf level to the community level based on six easily-measurable parameters, including leaf net photosynthetic rate, fresh leaf mass per unit leaf area, fresh weight of all plant leaves, the percentage of healthy leaves, the percentage of received effective light by leaves in the community, and community coverage. The community-level photosynthetic carbon assimilation and productivity all increased with warming, and the net photosynthetic rate at the leaf level was significantly higher than at the community level. Under elevated temperature, the net photosynthetic rate of E. nutans decreased, while that of P. anserina increased. Conclusions: These results indicated that climate warming may significantly influence plant carbon assimilation, which could alter alpine meadow community composition in the future.